Analisis perencanaan dan pengendalian persediaan bahan baku menggunakan klasifikasi ABC dan Metode Min-Max Stock - Azhima, Fauzan (Program Studi Teknik mesin, Fakultas Teknik, Universitas Al Azhar Medan, 2023)
Inventory is one of the assets contained in the company. Stock plays an essential role for companies because Inventory must be planned and controlled properly. Inventory control is seeking the availability of raw materials so that there are no shortages and excesses. ABC classification is a method used to classify goods based on the ranking or order of the cumulative percentage value of absorption of funds and the cumulative percentage of raw material use, which are then sorted from the highest importance to the lowest value and are divided into groups A, B and C. Inventory is carried out to exercise control using Min-Max Stock; if the stock has exceeded the minimum limit, then a Re-Order must be made, and the maximum limit is the availability limit. The results of the ABC classification with the cumulative percentage of capital absorption and the percentage of use of raw materials show that the factory must focus on paying attention to handling the availability of suitable materials so that no buildup can cause damage and its availability is maintained. Proper handling so that the raw materials are not damaged due to accumulation and to avoid running out of raw materials, the Min-Max Stock method takes into account the amount of Safety Stock that must be in storage so that the production process can run smoothly if there is an additional need for raw materials or occurs late arrival of raw materials. In addition, so that there is no accumulation of raw materials in storage